Development of approaches to the evaluation of pharmacotherapy effectiveness for chronic hepatitis C - I. A. Narkevich; E. A. Tsitlionok (IRBIS LLC, 2024)
Objective: to analyse the consumption pattern of antiviral therapy (AVT) for chronic hepatitis C on the example of an infectious hospital.Material and methods. The study was based on data from 380 discharge summaries of an infectious diseases hospital for 2011-2019. The criterion of sampling was the established diagnosis of chronic hepatitis C. The first line therapy regimens were analyzed and compared; the calculations were based on direct treatment costs of the study sample. The pharmacoeconomic effectiveness of therapy was assessed by calculating the cost-effectiveness ratio (CER).Results. A retrospective analysis of patients' sampling allowed to establish a general profile: a 40-year-old man with hepatitis C virus genotype 1 and a mild degree of liver fibrosis. A total of 18 international nonproprietary names (17 trade names) were used for AVT. The pattern of drugs prescribed correlated with the clinical guidelines for the studied period and allowed to distinguish the beginning of the transition from interferonbased regimens to direct-acting antivirals (DAAs). The change in the treatment paradigm was associated not only with increased efficacy in achieving a sustained virologic response, but also with minimization of side effects. The high frequency of prescribing interferon regimens as AVT was accompanied by low rates of achieving virus elimination (63.69%), high frequency of relapses (12.88%), as well as the lack of response to pharmacological correction (21.32%) and premature discontinuation of therapy due to adverse events (2.11%). A total of 142,450,414.91 rubles was spent on the first line pharmacotherapy in the study cohort during the study period. Costs per 1 patient with the diagnosis "chronic hepatitis C" and F0-F3 fibroses according to METAVIR were 372,847.07 rubles with achieving sustained virologic response without relapse in 66% of cases, costs per patient with F4 liver lesion were 398,464.73 rubles (45,16%, respectively).Conclusion. The findings allow us to note the transition from interferon-, nucleoside- and nucleotide-based drugs to DAAs, which can be associated with an increase in therapy effectiveness and proportion of cases with sustained virologic response achieved along with a decrease in the number of adverse events. The results of the study have practical implications for building a strategy for hepatitis C virus elimination in terms of choosing effective pharmacotherapy while reducing the economic burden.